The critical role of agrin in the hematopoietic stem cell niche. - Mazzon, C; Anselmo, A; Cibella, J; Soldani, C; Destro, A; Kim, N; Roncalli, M; Burden, S; Dustin, M; Sarukhan, A; Viola, A (2011)
Hematopoiesis is the process leading to the sustained production of blood cells by hematopoietic stem cells (HSCs). Growth, survival, and differentiation of HSCs occur in specialized microenvironments called "hematopoietic niches," through molecular cues that are only partially understood. Here we show that agrin, a proteoglycan involved in the neuromuscular junction, is a critical niche-derived signal that controls survival and proliferation of HSCs. Agrin is expressed by multipotent nonhematopoietic mesenchymal stem cells (MSCs) and by differentiated osteoblasts lining the endosteal bone surface, whereas Lin(-)Sca1(+)c-Kit(+) (LSK) cells express the α-dystroglycan receptor for agrin. In vitro, agrin-deficient MSCs were less efficient in supporting proliferation of mouse Lin(-)c-Kit(+) cells, suggesting that agrin plays a role in the hematopoietic cell development. These results were indeed confirmed in vivo through the analysis of agrin knockout mice (Musk-L;Agrn(-/-)). Agrin-deficient mice displayed in vivo apoptosis of CD34(+)CD135(-) LSK cells and impaired hematopoiesis, both of which were reverted by an agrin-sufficient stroma. These data unveil a crucial role of agrin in the hematopoietic niches and in the cross-talk between stromal and hematopoietic stem cells.